Central banks and inflation: where do we stand and how did we get here? - Karl Whelan (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
The inability of central banks to attain their target inflation rates in recent years has raised questions about the extent to which central banks can control the inflation process. This paper discusses the evolution of thought and evidence since the 1960s on the determinants of inflation and the role that should be played by central banks. The paper highlights the roles played by two streams of thought associated with Milton Friedman: monetarist theories predicting a key role for monetary aggregates in determining inflation and the rise in popularity of the expectations-augmented Phillips curve. The author discusses the influence of the latter in determining the modern consensus on central-bank institutions and the relative roles for fiscal and monetary policies. The paper concludes with a discussion of macroeconomic developments since 2010 and current policy options to stimulate the economy and restore inflation to its target levels, including the merits of 'helicopter money'.
Keywords: E31; E52; E58; 330; inflation; central banks; Phillips curve; Milton Friedman